Colombian universities incorporate PlaSA Colombia as a pedagogical tool to promote food system education among young people - Rankin, Sara; Gonzalez, Carlos; Castillo, Johana (2025)
The Alliance-developed PlaSA Colombia platform enhances education on food systems through interactive, data-driven learning experiences, making complex concepts more accessible and engaging. Integrated into curricula at Pontificia Universidad Javeriana and ICESI University, the platform has improved students’ and educators’ capacity to analyze sustainability challenges. Over 190 participants engaged in experiential learning activities, fostering critical thinking and informed decision-making on food choices. Institutional adoption and expansion plans demonstrate its scalability, while interdisciplinary collaboration has strengthened its impact, making PlaSA Colombia a replicable model for transforming food systems education.